PELATIHAN TENTANG MODIFIKASI PENANGANAN LIMBAH RS DI RSU SEMBIRING - Martha Arizona; Linda Margata; Sarah Damayanti (INSTITUT KESEHATAN DELI HUSADA, 2021)
As one of the most important health service departments, the hospital always produces medical solid waste and non-medical solid waste in daily activities, especially in the inpatient department, specialist room section, general clinic section, specialist clinic room, dental clinic room, maternal and child care, laboratory clinics and pharmacies. Most medical solid waste contains substances that are highly contagious, infectious and dangerous. Therefore it must be managed properly, otherwise these wastes will become a new source of transmission for both the community around the hospital and for medical personnel in the hospital. The management and handling of hospital waste has special rules. By improving the handling and management of hospital waste, medical waste management, increasing knowledge of human resources in waste management, and its impacts can influence the creation of examples of healthy development from a healthy society by improving the quality of individual and community health. Hospital medical solid waste and the poor quality of the hospital environment are the causes of various health problems, therefore it is necessary to apply laws and regulations to monitor various environmental factors in accordance with hygienic principles of environmental cleanliness. This training and counseling proposes a medical solid waste management model at the Sembiring General Hospital to create a healthy environment around the hospital.